Whose memory? –The Story of Trajectory of an Yugoslavian Family in the Camps of Italy during the World War II - Barkay, Rafaela (2013)
During World War II, the family Dohan/Sprung fleeing from the Nazi persecution of Jews in the former Yugoslavia was detained by the Italian army and taken to Italy. Held initially in a small village in the north of the country where their life often mingled with the peasants of the region, they were taken later to the concentration camp of Ferramonti in the south. When it was liberated by the American soldiers, they went to Sicily and finally to Rome, where they could live in freedom. Some years later, the family immigrated to Brazil. The report of this journey through the eyes of one of the daughters is the focus of this article.